Role of Corn Silage in the Sustainability of Dairy Buffalo Systems and New Perspective of Allocation Criterion - Andrea Bragaglio; Aristide Maggiolino; Elio Romano; Pasquale De Palo (Agriculture, 2022)
This paper aims to compare the cradle-to-farm gate sustainability of two dairy buffalo systems, according to life cycle assessment guidelines (LCA). Primary data were obtained by five intensive farms with feeding plans based on non-corn silage (NCS) and five with corn silage (CS) based rations. Both systems were characterized by the presence of two farms with wheat grain yields, sold for human consumption. All the farms were in Southern Italy and seven were included in the Protected Designation of Origin (PDO) area of “Mozzarella di bufala campana”. The functional unit (FU) adopted was 1 kg of normalized buffalo milk (NBM); impact categories investigated were: global warming potential (GWP), acidification potential (AP), eutrophication potential (EP), agricultural land occupation (ALO), water depletion (WD). Two different economic allocation procedures were tested: a first step aimed to mitigate the environmental impacts sharing among wheat grain, where present, and milk. The second stage involved culled buffalo cows. Neither the allocation nor the combination of allocation and feeding system showed significant effects (p > 0.05). Corn silage-based system (CS) showed lower impacts than non-corn silage (NCS) one for AP and EP (p = 0.002 and p = 0.051 respectively). High average dry matter yield per hectare of corn silage probably had a positive effect on SO2 and PO43− equivalents.